Coronavirus HKU15 in respiratory tract of pigs and first discovery of coronavirus quasispecies in 5′-untranslated region - Woo, Patrick CY (Emerg Microbes Infect, 2017)
Coronavirus HKU15 is a deltacoronavirus that was discovered in fecal samples of pigs in Hong Kong in 2012. Over the past three years, Coronavirus HKU15 has been widely detected in pigs in East/Southeast Asia and North America and has been associated with fatal outbreaks. In all such epidemiological studies, the virus was generally only detected in fecal/intestinal samples. In this molecular epidemiology study, we detected Coronavirus HKU15 in 9.6% of the nasopharyngeal samples obtained from 249 pigs in Hong Kong. Samples that tested positive were mostly collected during winter. Complete genome sequencing of the Coronavirus HKU15 in two nasopharyngeal samples revealed quasispecies in one of the samples. Two of the polymorphic sites involved indels, but the other two involved transition substitutions. Phylogenetic analysis showed that the two nasopharyngeal strains in the present study were most closely related to the strains PDCoV/CHJXNI2/2015 from Jiangxi, China, and CH/Sichuan/S27/2012 from Sichuan, China. The outbreak strains in the United States possessed highly similar genome sequences and were clustered monophyletically, whereas the Asian strains were more diverse and paraphyletic. The detection of Coronavirus HKU15 in respiratory tracts of pigs implies that in addition to enteric infections, Coronavirus HKU15 may be able to cause respiratory infections in pigs and that in addition to fecal-oral transmission, the virus could possibly spread through the respiratory route. The presence of the virus in respiratory samples provides an alternative clinical sample to confirm the diagnosis of Coronavirus HKU15 infection. Quasispecies were unprecedentedly observed in the 5′-untranslated region of coronavirus genomes.